Peri-Implant Oral Squamous Cell Carcinoma in a Non-Smoking, Non-Alcoholic Patient: A Case Report - Bakhshi, Mahin; Dalirani, Sara; Mir Mohammad Sadeghi, Hassan; Atarbashi Moghadam, Saede; Kashefi baher, Mohammadreza (Journal of Dental School, 2025)
Background and Objectives: Oral squamous cell carcinoma (OSCC) accounts for over 90% of oral cancers and is traditionally associated with risk factors such as tobacco, alcohol, and HPV. Chronic inflammation and mechanical irritation, including peri-implantitis, may contribute to carcinogenesis, with early malignant lesions often mimicking peri-implantitis, leading to delayed diagnosis. This case report underscores the importance of vigilant monitoring of peri-implant lesions by presenting a case of OSCC development in a non-smoker, non-alcoholic patient in the peri-implant region. Case Presentation: An 84-year-old man presented with a three-month history of gingival problems. His medical history included prior heart surgery and current medications of Aspirin, Losartan, and Carvedilol. He had no history of smoking or alcohol consumption. Five years earlier, a dental implant was placed in the anterior left mandible. Based on the information provided by the patient, the implant was removed three months ago due to gingival complications; however, the precise reason for this decision remains unclear, as the patient presented to us after the implant had already been removed. Intraoral examination revealed an exophytic lesion with a granular surface and central ulceration on the left mandibular edentulous ridge, extending buccally into the vestibular depth, lingually toward the floor of the mouth, mesially to the midline, and distally to the molar region. Radiographs showed a localized radiolucent lesion with poorly defined, non-corticated borders in the left mandibular canine-premolar region. An incisional biopsy was performed due to suspicion of malignancy. Histopathological evaluation confirmed the diagnosis of OSCC. Conclusions: Vigilant follow-up of implant patients is crucial for identifying and managing peri-implant lesions to prevent potential malignant transformation. Further research is required to clarify the potential etiological factors underlying the relationship between dental implants and OSCC, providing valuable insights to refine clinical guidelines.